2019
DOI: 10.1111/1759-7714.13083
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase and baseline markers associated with clinical outcomes of advanced esophageal squamous cell carcinoma patients treated with camrelizumab (SHR‐1210), a novel anti‐PD‐1 antibody

Abstract: Background A small proportion of patients with advanced esophageal squamous cell carcinoma (ESCC) could benefit from immune checkpoint inhibitors; however, reliable peripheral blood biomarkers for outcomes of anti‐PD‐1 immunotherapy in ESCC have not been identified. Methods The data of 43 patients in the ESCC cohort of a phase I trial at our center were retrospectively reviewed. All patients were administered intravenous camrelizumab (SHR‐1210), a novel anti‐PD‐1 antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…Neutrophil count and LDH both routinely detected the hematological index and were easily available in our clinical practice. Previous studies have investigated the prognostic value of LDH level, neutrophil count, and NLR in many solid tumors (10,21,24). However, there was no investigation about the role of the LDH level combined with neutrophil count or NLR in the prognosis of ESCC patients treated with radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophil count and LDH both routinely detected the hematological index and were easily available in our clinical practice. Previous studies have investigated the prognostic value of LDH level, neutrophil count, and NLR in many solid tumors (10,21,24). However, there was no investigation about the role of the LDH level combined with neutrophil count or NLR in the prognosis of ESCC patients treated with radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis investigating the prognostic value of the LDH level in solid tumors showed that a high LDH level is associated with poor survival in melanoma, gastric, lung cancer, prostate, and renal cell carcinomas (34). Recently, a high LDH level has been demonstrated to effectively predict the response to cancer treatment, such as chemotherapy (11), anti-angiogenetic agents (35), and checkpoint immunotherapy (22,24) in various cancers. The prognostic role of the LDH level was also investigated in ESCC patients who underwent curative treatment in the study from Wei et al (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14]25 Several studies also have evaluated the prognostic value of LDH in ESCC. [15][16][17][18][19][20] Nevertheless, the prognostic role for pretreatment serum LDH in ESCC remains uncertain until now. The current study demonstrated that lower LDH levels were associated with a better prognosis compared with higher LDH levels, as shown in both multivariable analysis based on the whole cohort of 614 patients and the propensity score-matched cohort of 256 patients.…”
Section: Discussionmentioning
confidence: 99%
“…14 Several investigators also scrutinized the prognostic value of LDH in ESCC. [15][16][17][18][19][20] However, owing to the inconsistent conclusions, serum LDH is a controversial prognostic biomarker for prognosis in ESCC and needs to be further investigated. Furthermore, studies on the in uence of LDH on the prognosis are still lacking for patients with ESCC underwent chemoradiotherapy.…”
Section: Introductionmentioning
confidence: 99%